Implementation of animal welfare in tiger sanctuary, Barumun Nagari Wildlife Sanctuary, North Sumatra, Indonesia - ronna saab; Pahrian Ganawira Siregar; Tatang Mitra Setia (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Saab R, Siregar PG, Tatang Mitra Setia TM. 2019. Implementation of animal welfare in tiger sanctuary, Barumun Nagari Wildlife Sanctuary, North Sumatra, Indonesia. Biodiversitas 20: 2790-2795. The accelerated growth in the development of economic and social infrastructure has drastically diminished the population of Sumatran tiger (Panthera tigris sumatrae) and its habitat. As a result, conflicts between tigers and humans are increasing rapidly in recent years. The wild tigers in conflict, such as those that attack humans and livestock, are usually killed or captured, while those who cannot return to the forest due to injury or illness are then translocated to the zoo. The increasing number of human and tiger conflicts raises the need for special facilities, such as sanctuaries, to recover the condition of the tigers, before they are released to the wild. This study aimed to examine the aspects of welfare management and assess the level of welfare of the tigers kept in the sanctuary at the Barumun Nagari Wildlife Sanctuary (BNWS) in North Sumatra, Indonesia. The study was carried out from March to April 2019, while data collection was carried out by literature studies, field observation on implementation of five animal welfare parameters, and self-assessment by the manager of the sanctuary. The results showed that, on a score from 1 to 5, the animal welfare parameter scores were 4.88 (freedom from hunger and thirst), 4.81 (freedom to express natural behavior), 4.79 (freedom from discomfort), 3.81 (freedom from fear and distress) and 3.69 (freedom from pain, injuries, and diseases). The total achievement implementation value of animal welfare in BNWS was 89.13, or very good. However, some improvements still have to be made by the sanctuary manager to enhance the animal welfare of tigers in BNWS.